Student Responses to Using Microsoft Teams in Online Learning at Elementary Schools - Suyanti Suyanti; Dian Nur Antika Eky Hastuti (Universitas PGRI Yogyakarta, 2023)
The research is based on student responses to online learning by the teacher using the Microsoft Teams application. This type of research is qualitative case study. The research subjects were 2 students in grade III. Data collection by questionnaires and interviews. Data analysis with data reduction, data presentation, and drawing conclusions. The results of the research on student responses in cognitive dimensions of understanding aspects: easy to understand the content of the material using the Microsoft Teams application, quickly understand the content of the material, easy to remember the material using the Microsoft Teams application through the file feature. Aspect of clarity: reading instructions for doing assignments clearly, prefers to work using the Assigment Feature. The affective dimension of the motivational aspect is always given a motivational sentence for doing assignments through the Microsoft Teams application by the teacher, doing assignments on their own and asking friends, doing quizzes on their own without asking their parents. Interesting aspect: interested in presenting material using the Microsoft Teams application, learning like face-to-face with classmates. Through the video conferencing feature. Curiosity aspect: asking the teacher using the Microsoft Teams application on a daily life event related to the subject matter. The conative dimension of the tendency aspect: tends to ask questions, pages, materials using the Microsoft Teams application, tends to ask questions via chat or video conferencing features.